2012
DOI: 10.1007/s00408-012-9435-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, Asthma, Smoking and Acute Chest Syndrome in Young Adults with Sickle Cell Disease

Abstract: Our results indicate that young adults with SCD should be discouraged from smoking and their asthma aggressively treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…The aforementioned studies focused on subjective report of exposure in children's home environments and may not have sufficiently captured other places in which children are frequently exposed to tobacco smoke (such as regular childcare arrangements, the homes of close friends and relatives, or split-parent households) and likely underestimate the effect of tobacco smoke exposure. Further, smoking (also by self-report) has been associated with fivefold increased risk of death in young adults with SCD [24].…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned studies focused on subjective report of exposure in children's home environments and may not have sufficiently captured other places in which children are frequently exposed to tobacco smoke (such as regular childcare arrangements, the homes of close friends and relatives, or split-parent households) and likely underestimate the effect of tobacco smoke exposure. Further, smoking (also by self-report) has been associated with fivefold increased risk of death in young adults with SCD [24].…”
Section: Discussionmentioning
confidence: 99%
“…The strong association between lung disease and SCA-related mortality has been well-established [3][4][5]13,26,27 ; however, what is not known is whether pulmonary function results are associated with earlier death. For the first time, we have demonstrated that FEV 1 % predicted can be used to predict earlier death in individuals with SCA.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest prospective cohort study investigating the natural history of sickle cell disease (SCD) in children and adults, the Cooperative Study of Sickle Cell Disease (CSSCD), Platt et al 1 noted an increased risk of earlier death in patients with SCA was associated with acute chest syndrome (ACS), renal failure, seizures, an elevated baseline white cell count, and a low level of fetal hemoglobin (Hb). Since that report, end-stage renal disease requiring dialysis, 2 the presence of asthma [3][4][5] and/or wheezing, 6 smoking, 5 N-terminal (NT)-pro brain natriuretic peptide levels, 7 right heart catheter-confirmed pulmonary hypertension along with the physiological severity of the precapillary pulmonary hypertension, 8,9 and severity of hemolysis [10][11][12] have all been associated with earlier death among individuals with SCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In individuals with SCD, asthma is associated with increased frequency of pain episodes and ACS [96], as well as significantly higher mortality [94,97]. This was most clearly demonstrated in data from the CSSCD cohort where 1,963 individuals with SCA who were classifiable for asthma were followed for a total of 18,495 patientyears.…”
Section: Pulmonary Complicationsmentioning
confidence: 99%